Succinylated gelatin substantially increases en bloc resection size in colonic EMR: a randomized, blinded trial in a porcine model - Moss, Alan; Bourke, Michael J.; Kwan, Vu; Tran, Kayla; Godfrey, Craig; McKay, Gary; Hopper, Andrew D. (Gastrointestinal endoscopy, 2010)
Succinylated gelatin (SG) is an inexpensive colloid that may combine ease of use with the advantages of a colloid to potentially increase EMR specimen size, leading to a higher rate of en bloc resection. To evaluate the safety, efficacy, and impact on EMR specimen size of SG as a submucosal (SM) injectant in comparison with normal saline solution (NS). Randomized, blinded, controlled trial conducted with Animal Ethics Committee approval. Academic hospital. Ten swine. Sixty EMRs (30 using SG vs 30 using NS as 3 paired experiments per animal) of the largest possible en bloc snare resection of normal colonic mucosa after SM injection of a fixed volume of either SG or NS. EMR specimen size, duration of SM cushion, duration of procedure, ratio of vertical elevation to lateral spread of injectant, ease of resection, adverse effects, perforation, histopathology of EMR sites in colectomy specimens at necropsy (for inflammatory cell content, depth of ulceration, and vascular or ischemic changes). The mean subject weight was 53 kg. The mean EMR specimen dimensions and surface area were significantly larger with SG (length 37 vs 31 mm, P = .031; width 32 vs 26 mm, P = .022; surface area 9.5 cm 2 vs 6.7 cm 2, P = .044, respectively). The median SM cushion duration was 60 minutes with SG versus 15 minutes with NS ( P = .005). The median procedure duration with SG was 2.6 minutes vs 2.5 minutes with NS ( P = .515). The ratio of vertical elevation to lateral spread of injectant (mean score on a 3-point scale) was 3 with SG versus 2 with NS ( P = .228). Ease of resection score (mean score on a 10-point scale) was 8 with SG versus 7 with NS ( P = .216). There were no systemic adverse effects, hypersensitivity reactions, or bleeding episodes. There were 2 perforations (treated with clips) with SG and 1 with NS ( P = 1.0). Blinded histopathologist assessment of necropsy colectomy specimens did not identify any significant differences between SG and NS EMR sites. Animal study. SG is safe and results in a 42% increased surface area for en bloc EMR. Given its other favorable properties, it represents a significant step toward defining the ideal EMR solution.